Bridging the knowledge gap: accessibility of SRHR information, services and competences of health facilities for adolescents and their care givers in rural Eastern Uganda - Kagurusi, Patrick; Osinde, Stephen Omejja; Kwikiriza, Benson; Elizabeth, Nagawa; Ajok, Dolly; Kapsandui, Tonny; Nankanja, Maureen (BMC Public Health 25, 2025)
Introduction A quarter of Uganda’s population is aged 10–19 years and majority live in rural areas. Access to sexual and reproductive health services and rights (SRHR) remains a challenge among this population, contributing to a high teenage pregnancy rate of 24.9% in rural Uganda. The study assessed the accessibility of SRHR information, services and competences of health facilities among adolescents and their care givers in Namutumba and Bugiri districts. Methods A cross-sectional study was conducted. 473 respondents were systematically and randomly recruited after informed consent and/ assent. Data were collected using a pre-tested electronic questionnaire and analyzed using STATA version 14. Descriptive statistics were used to summarize the SRHR indicators. Ethical approval was obtained before data collection. Results 51% of participants were aged between 10 and 19 years. Only 22.6% [107/473, CI:17.7–25.1] of participants had received at least three out of the 13 forms of SRHR/SGBV information. Females significantly had higher access to SRHR information compared to males [24.6%, 95% CI: 19.7–30.3, P-value-0.049]. There was no significant differences in the access of SRHR between adolescents and their caretakers. Approximately 41.9% [198/473, CI: 36.2–45.1] agreed to at least three of the eight SRH rights. Half of adolescents had experienced at least one of the nine forms of SGBV, yet only 27% [34/126, CI: 24.3,32.7] shared their experience. Only one health facility offered more than 8 family planning methods and none provided comprehensive SRHR services daily to adolescents. There were no significant differences in the competencies of health facilities between Bugiri and Namutumba districts. Conclusion This study highlights significant gaps in access to SRHR and SGBV services, with limited awareness on SRHR/SGBV and inadequate reporting of SGBV cases due to stigma. Strengthening community support systems,
© The Author(s) 2025. Open Access This article is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License, which permits any non-commercial use, sharing, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if you modified the licensed material. You do not have permission under this licence to share adapted material derived from this article or parts of it. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence,
Keywords: Sexual and reproductive health and rights; Sexual gender based violence; Adolescent; Teenage pregnancy